1997
DOI: 10.1021/js9701667
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Investigations of Erythromycin A Dihydrate: Structure, NMR Spectroscopy, and Hygroscopicity

Abstract: The crystal structures of the commercially available form of erythromycin A dihydrate and clarithromycin anhydrate, in addition to the structure of erythromycin B dihydrate, are reported in this paper. In light of the crystallographic data, analysis of the structural information provides insight into the physical properties of these pharmaceuticals. The propensity of these pharmaceuticals to form solvated structures is discussed and the hygroscopicity of erythromycin A dihydrate is investigated. Solid-state 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 11 publications
3
42
0
Order By: Relevance
“…A number of studies on these forms have been reported. [4][5][6][7][8][9][10][11] At the same time, a literature review showed that similar information on commercially marketed lots of Em raw material is often lacking, and significant variations in the physical properties of the bulk drug are encountered among material supplied by some manufacturers and among different lots supplied by the same manufacturer. 6 Additionally, the intricate molecular structure of Em (Figure 1) suggests the variety of possible supramolecular motifs in crystals, resulting in the formation of different polymorphic modifications.…”
Section: -3mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies on these forms have been reported. [4][5][6][7][8][9][10][11] At the same time, a literature review showed that similar information on commercially marketed lots of Em raw material is often lacking, and significant variations in the physical properties of the bulk drug are encountered among material supplied by some manufacturers and among different lots supplied by the same manufacturer. 6 Additionally, the intricate molecular structure of Em (Figure 1) suggests the variety of possible supramolecular motifs in crystals, resulting in the formation of different polymorphic modifications.…”
Section: -3mentioning
confidence: 99%
“…8,13 It is a clathrate where large molecules of Em play the role of "hosts" and small molecules of water play the role of "guests" occupying periodic voids in the crystal. It was hypothesized that solvates obtained in the present study have an analogous-that is, a clathrate-structure.…”
Section: Xrpdmentioning
confidence: 99%
“…Unexpectedly, the hydrated form of acyclovir solubilizes more rapidly than the anhydrous form (Kristl et al, 1996;Stephenson et al, 1997), which is explained by the high thermodynamic stability and low hygroscopicity of the anhydrous form (Kristl et al, 1996).…”
Section: Acyclovirmentioning
confidence: 99%
“…In addition to being easily controllable, the more stable polymorphic form also complies with requirements described in the Q6A Guide of the International Commission on Harmonization (ICH) for solid form selection (Grant et al, 2004). Kristl et al, 1996;Sohn et al, 2008;Lutker et al, 2011;Tutughamiarso et al, 2012) Acetylsalicylic Acid Analgesic IV 2 I (TSRL inc, 2012; Klein et al, 1994;Vishweshwar et al, 2005;Bond et al, 2011) Ibuprofen Analgesic II 2 I (TSRL inc, 2012;Shankland et al, 1996;Erk et al, 2004;Stone et al, 2009;Derollez et al, 2010) Acetaminophen Analgesic IV 6 I (TSRL inc, 2012;Haisa et al, 1974;Naumov et al, 1998;McGregor et al, 2002;Parkin et al, 2002;Peterson et al, 2002;Fabbiani et al, 2004 (Otsuka et al, 1983;Stephenson et al, 1998;Kennedy et al, 2003;Kasim et al, 2004;Aguiar et al, 2011) Ciprofloxacin Antibiotic III 3 II (hydrate) (TSRL inc, 2012;Turel et al, 2003;Fabbiani et al, 2008;Fabbiani et al, 2009;Fabbiani et al, 2011) Doxycycline Antibiotic IV 2 ‡ (TSRL inc, 2012; Legendre et al, 2012) Erythromycin Antibiotic IV 4 Dihydrate (TSRL inc, 2012;Fukumori et al, 1983;Stephenson et al, 1997;Miroshnyk et al, 2006) Sulfamethoxazole Antibiotic IV 4 III (hemihydrate) (TSRL inc, 2012;…”
Section: Bioequivalence and Bioavailabilitymentioning
confidence: 99%
“…[1][2][3] The interaction of water with pharmaceuticals plays an especially important role in many aspects of drug development, from synthetic design and dosage form to effective product packaging and drug bioavailability. Therefore, many investigators [4][5][6][7][8] have reported the moisture sorption kinetics for pure crystalline forms and/or mixtures of unstable crystalline forms of pharmaceuticals under conditions of relatively high humidity. The US Food and Drug Administration (FDA) reported that the in vitro dissolution rate of a commercial carbamazepine (CBZ) preparation that had been exposed to 97% relative humidity (RH) for 2 weeks was up to one third smaller than that of an unexposed preparation.…”
Section: Introductionmentioning
confidence: 99%